2018
DOI: 10.1097/spv.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anorectal Manometry Testing in Left Lateral and Lithotomy Positions

Abstract: Objectives: Anorectal manometry (ARM) is typically performed in left lateral position, but many practitioners are more familiar with the lithotomy position. We aimed to evaluate agreement between anorectal manometry performed in left lateral and lithotomy positions and patient preference for testing position. Methods:We performed a prospective comparison study of left lateral versus lithotomy position for women undergoing ARM for the evaluation of fecal incontinence. Women were randomly assigned to undergo tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
1
Order By: Relevance
“…Studies on the effect of posture on rectal volume are limited. Halani et al [21] reported that although there was no signi cant difference in the rectal volume measured in the left-lateral position compared with the lithotomy position in female FI patients, higher values for the measurements were observed in lithotomy than in the left-lateral position. Another study of urogynecological patients reported similar results [22].…”
Section: Discussionmentioning
confidence: 95%
“…Studies on the effect of posture on rectal volume are limited. Halani et al [21] reported that although there was no signi cant difference in the rectal volume measured in the left-lateral position compared with the lithotomy position in female FI patients, higher values for the measurements were observed in lithotomy than in the left-lateral position. Another study of urogynecological patients reported similar results [22].…”
Section: Discussionmentioning
confidence: 95%
“…Studies on the effect of posture on rectal sensation are limited. Halani et al [ 25 ] reported that although there was no significant difference in the rectal volume measured in the left-lateral position compared with the lithotomy position in female FI patients, higher values for the measurements were observed in lithotomy than in the left-lateral position. Another study of urogynecological patients reported similar results [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, DDV and MTV were signi cantly higher in the erect position than in the left-lateral position in the 80 FI patients. The reason is unclear however, but testing was performed in the same sequence as previous studies [21,22], rst in the left-lateral position and then in the lithotomy position, which may have blunted rectal sensation during rectal capacity examination in the erect position. The order of examination should be reversed and re-examined in the future.…”
Section: Discussionmentioning
confidence: 99%
“…В литературе также существует мнение об эффективности определения анального давления покоя и давления сжатия в литотомическом положении. Однако данная модификация на данный момент не введена в клиническую практику, поскольку не отразила пользы для мониторинга ректальной чувствительности [50].…”
Section: методы оценки снпрunclassified